Accounting for molecular flexibility in photoionization: case of tert-butyl hydroperoxide. Issue 18 (29th April 2022) - Bourgalais, Jérémy; Jiang, Zhongming; Bloino, Julien; Herbinet, Olivier; Carstensen, Hans-Heinrich; Garcia, Gustavo A.; Arnoux, Philippe; Tran, Luc-Sy; Vanhove, Guillaume; Nahon, Laurent; Battin-Leclerc, Frédérique; Hochlaf, Majdi
Abstract : We use synchrotron-based VUV single photon ionization and advanced theoretical simulations to unravelling the dissociative ionization of tert -butyl hydroperoxide where special treatment is undertaken because of the flexibility of this molecule. Abstract : tert -Butyl hydroperoxide ( t BuOOH) is a common intermediate in the oxidation of organic compounds that needs to be accurately quantified in complex gas mixtures for the development of chemical kinetic models of low temperature combustion. This work presents a combined theoretical and experimental investigation on the synchrotron-based VUV single photon ionization of gas-phase t BuOOH in the 9.0 - 11.0 eV energy range, including dissociative ionization processes. Computations consist of the determination of the structures, vibrational frequencies and the energetics of neutral and ionic t BuOOH. The Franck–Condon spectrum for the t BuOOH + ( X + ) + e − ← t BuOOH ( X ) + hν transition is computed, where special treatment is undertaken because of the flexibility of t BuOOH, in particular regarding the OOH group. Through comparison of the experimental mass-selected threshold photoelectron spectra with explicitly correlated coupled cluster calculations and Franck–Condon simulations that account for the flexibility of the molecule, an estimation of the ionization energy is given. The appearance energy of the only fragment observed within the above-mentioned energy range, identified as the tert -butyl C4 H9 +, is also reported. Finally, the signal branching ratio between the parent and the fragment ions is provided as a function of photon energy, essential to quantify t BuOOH in gas-phase oxidation/combustion experiments via advanced mass spectrometry techniques.